Preparation of Nanoscrolls by Rolling up Graphene Oxide–Polydopamine–Au Sheets using Lyophilization Method. Issue 12 (1st June 2016) - Yang, Yongfang; Zhang, Xiaolu; Wang, Hefang; Tang, Honghao; Xu, Lidong; Li, Hua; Zhang, Lei
Abstract: Graphene oxide–polydopamine–Au (GO–PDA–Au) nanoscrolls were prepared by rolling up GO–PDA–Au sheets through a simple lyophilization method. The structure of GO–PDA–Au nanoscrolls and GO–PDA–Au sheets were compared by powder X‐ray diffraction, Raman spectra, transmission electron microscopy, and scanning electron microscopy. The results demonstrated that the heterogeneous GO–PDA–Au nanoscrolls were synthesized successfully. Polydopamine (PDA) attached at the surface of GO sheets served as binding reagents to anchor and disperse Au nanoparticles (NPs). The electrocatalytic activity of methanol with GO–PDA–Au nanoscrolls and GO–PDA–Au sheets as electrodes were conducted. Compared to GO–PDA–Au sheets, GO–PDA–Au nanoscrolls showed better electrocatalytic activity and electrochemical stability owing to their scrolled structure. This article provides a simple and effective method to prepare GO nanoscrolls containing metal NPs that broadens the applications of the graphene‐based materials in optical, magnetic, and catalytic fields. Abstract : Scrolled structures : The heterogeneous graphene oxide‐polydopamine‐Au (GO–PDA–Au) nanoscrolls were prepared by rolling up GO–PDA–Au sheets through a simple lyophilization method. Polydopamine (PDA) attached at the surface of GO sheets served as binding reagents to anchor and disperse Au nanoparticles (NPs) uniformly (see scheme). Compared to GO–PDA–Au sheets, GO–PDA–Au nanoscrolls showed better electrocatalytic activity and electrochemical stability owing to their scrolled structure.